Selma and Lois DeBakey: Icons of Medical Preservation - Jeffrey S. Reznick (Methodist DeBakey Cardiovascular Journal)
INTRODUCTION In his 2016 article published in this journal, Dr. William Winters described Selma and Lois DeBakey as “icons of medical communication” who believed that “nothing hinders communication as much as words, when they are used badly or incorrectly.”1 This article bookends Winters’ description by explaining how Selma and Lois DeBakey were also “icons of medical preservation” who asked, “Shall we nourish the biomedical archives as a viable and indispensable source of information, or shall we bury their ashes and lose a century or more of consequential scientific history?”2 In addressing this question posed by Selma and Lois DeBakey and spotlighting their answers in their own engaging words, we highlight the relevance of their advocacy for the medical humanities and its influence to inform humanistic approaches to science and medicine. More broadly, their advocacy inspires us to appreciate the historical record as we think critically about how we communicate the experience of medicine and science, learn from it today, and preserve it for tomorrow.